2017
DOI: 10.1063/1.4989732
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dust-acoustic solitary waves and shocks in dusty plasmas with a pair of trapped ions

Abstract: Abstract:The propagation characteristics of small-amplitude dust-acoustic (DA) solitary waves (SWs) and shocks are studied in an unmagnetized dusty plasma with a pair of trapped positive and negative ions. Using the standard reductive perturbation technique with two different scaling of stretched coordinates, the evolution equations for DA SWs and shocks are derived in the forms of complex Korteweg-de Vries (KdV) and complex Burgers' equations. The effects of dust charge variation, the dust thermal pressure, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…2015 a ; Adhikary et al. 2017), and expand the variables , and , in power series of (Schamel 1973; Mamun & Shukla 2010; Adhikary et al. 2014): where stands for negative (positive) dust species.…”
Section: Mb Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…2015 a ; Adhikary et al. 2017), and expand the variables , and , in power series of (Schamel 1973; Mamun & Shukla 2010; Adhikary et al. 2014): where stands for negative (positive) dust species.…”
Section: Mb Equationmentioning
confidence: 99%
“…2015 b ; Adhikary et al. 2017) of the MB equation (3.19) is given by where , and are given by It is obvious that, as the speed increases, the amplitude (width) increases (decreases), and that the viscosity coefficient does not have any effect on the amplitude, but it does have significant effects on the width of the DA shock waves (as increases, the width of the DA shock waves increases significantly).…”
Section: Mb Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In negative ion contaminated dusty plasmas, characteristics of arbitrary amplitude dust-acoustic solitary waves have been investigated using the Sagdeev potential approach (Wang et al 2005). Propagation characteristics of small-amplitude dustacoustic solitary waves and shock waves in an unmagnetized dusty plasma with a pair of trapped positive and negative ions were investigated considering both positively and negatively charged dust grains (Adhikary et al 2017). The effects of non-steady dust charge variations and a weak magnetic field on small but finite amplitude nonlinear dust-acoustic waves in an electronegative dusty plasma consisting of electrons, positive ions, negative ions and dust grains were investigated and it was shown that the dynamics of the nonlinear waves is governed by the Korteweg-de Vries-Burger equation which possesses a dispersive shock wave (Ghosh, Ehsan & Murtaza 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental analysis [26] and computer simulations [27] have confirmed this phenomenon. Very recently, considering dust charge fluctuations, Adhikary et al [30] have studied weakly nonlinear DA solitary waves and shocks in dusty plasmas in the presence of a trapped pair of ions. Mirsa [8] investigated the effect of a trapped pair of ions on the nonlinear propagation of dust-acoustic (DA) waves in a magnetized dusty plasma without considering electrons by deriving a KdV-like equation.…”
mentioning
confidence: 99%